Art-Based Learning as a Pedagogical Strategy to Enhance Attention, Engagement, and Learning in Pathology Education Among Nursing Students. - Shanmugam, Valliammal; Porredi, Vijayalakshmi; Kathyayani, Bidadi Veerabadraiah (Investigación & Educación en Enfermería)
Objective. To evaluate the effect of an Art-Based Learning activity on attention, engagement, and immediate learning outcomes in pathology education among undergraduate nursing students. Methods. A post-test-only pre-experimental study was conducted among 85 second-year nursing students in South India (October 2025). During a pathology lecture on thrombosis, students participated in an unannounced 30-minute Art-Based Learning activity representing thrombus formation through poems, stories, riddles, drawings, and comics. Learning outcomes were assessed immediately using a formative knowledge tool and an Attention & Engagement Scale. Results. The mean knowledge score was 8.9 (Maximum possible = 10), indicating strong immediate learning. Engagement levels were consistently high across all scale items (4.24 to 4.48 of 5 of maximum possible), indicating strong student involvement in the learning activity. Conclusion. Art-based learning significantly enhanced attention, engagement, and immediate learning outcomes. Art-Based Learning may serve as an effective complementary strategy to traditional teaching by transforming abstract pathology concepts into meaningful, memorable learning experiences.